L’accès aux ressources universitaires de la population étudiante en situation de handicap émergent à la maîtrise et au doctorat au Québec - Sall, Mariata; Picard, France; Pilote, Annie (Canadian Journal of Higher Education, 2022)
The population of students with disabilities in higher education has grown significantly, accentuated by the massive influx of students with emerging disabilities (SWED: learning disabilities, mental health disabilities and developmental disabilities). From a sociological perspective, this article focuses on access to university resources and the factors that influence access to master's and doctoral programs for SWEDs. It is based on a secondary analysis of a Canadian survey. SWEDs have less access to certain university resources compared to their peers with physical disabilities (SWPD) or without disabilities (SWoD). Three factors that could potentially facilitate (positive conversion factors) or hinder (negative conversion factors) access to resources were considered. For example, satisfaction with research leadership, satisfaction with faculty relationships, and satisfaction with information about the availability of financial support were found to facilitate access to university resources for the entire student population.